BENTUK KOMUNIKASI GURU DALAM PROSES PEMBELAJARAN PADA DISABILITAS TUNARUNGU DI SMPLB NEGERI 2 DENPASAR - Sitorus, Irmei Febe; Sugiarica Joni, I Dewa Ayu; Alit Suryawati, I Gusti Agung (E-Jurnal Medium; Vol 1 No 1 (2017), 2017)
Each individual communicates to build relationships from one person to another. An interaction that has been using by society often uses words or linguistics. However, some emotions that come out of human sense organ may communicate different cue when conveyed the word . Richard L. Weaver II, states that words generally trigger one set of sensory devices such as hearing, whereas nonverbal communication can trigger a number of sense devices such as sight, smell, feeling (Dasrun, 2012: 110). The purpose of this study is to observe and describe the form of teacher communication applied in the learning process in schools that provide specialized in deaf education. This research was conducted to 6 secondary school teachers at SMPLB Negeri 2 Denpasar. The theory used in this research is the theory of accommodation. Based on the results of research in the field shows that there are 3 forms of communication, among others; verbal communication, nonverbal communication and total communication. In addition, SMPLB Negeri 2 Denpasar teachers also apply the Communication Development Service of Perceptions of Sound and Rhythm (PKPBI) which serves to train the hearing loss for deaf students and minimize the consequences of disable, aiming for deaf students can be better trained in distinguishing sound sources, Develop the ability to detect, recognize sounds, and to understand the meaning, can communicate and interact with others.   Keywords: verbal communication, nonverbal communication, deaf